Relationship between Knowledge Management and Organizational Performance: A Test on SMEs in Malaysia - Ha, Shiaw-Tong; Lo, May-Chiun; Wang, Yin Chai (Elsevier Ltd., 2016)
Generally, small and medium enterprises (SMEs) play a crucial role in supporting the nation’s economy. Nevertheless, Malaysian SMEs have not developed their full potential. Therefore, it is essential for the entrepreneurs to search for and shift towards better strategies to become more successful. In the present turbulent environments, knowledge has been viewed as a major strategic competitive resource. Given the importance of knowledge, entrepreneurs are encouraged to develop their capabilities to manage knowledge which will move them to become more competitive and innovative. Extensive research is available in the knowledge management literature investigating the process of knowledge management as a composite construct; nonetheless little research has been done to examine the independent effects of the individual dimensions of knowledge management process. In particular, little empirical evidence has been found to determine the implementation of knowledge management practices in the context of developing countries and small business. This study aimed to fill the perceived gaps by investigating the relationship between knowledge management process capabilities and organizational performance in the context of Malaysian SMEs. Knowledge management process capabilities were conceptualized as four dimensional constructs: knowledge acquisition, knowledge conversion, knowledge application, and knowledge protection while organizational performance were divided into two dimensions namely, non-financial performance and financial performance. This paper anticipates that the four knowledge management process capabilities are important antecedents of organizational performance, which have in turn a positive relationship with both non-financial performance and financial performance of SMEs. The findings of this study will provide insights to entrepreneurs and help them to identify and develop effective strategies towards enhancing their overall performance.